Impact of Repeated Clot Retrieval Attempts on Infarct Growth and Outcome After Ischemic Stroke. (3rd August 2021) - Ben Hassen, Wagih; Touloupas, Caroline; Benzakoun, Joseph; Boulouis, Gregoire; Bretzner, Martin; Bricout, Nicolas; Legrand, Laurence; Rodriguez, Christine; Le Berre, Alice; Seners, Pierre; Turc, Guillaume; Cordonnier, Charlotte; et al.
Abstract : Objective: To determine whether the association between increasing number of clot retrieval attempts (CRA) and unfavorable outcome is due to an increase in emboli to new territory (ENT) and greater infarct growth (IG) in successfully recanalized patients with acute ischemic stroke due to large vessel occlusion (AIS-LVO). Methods: Data were extracted from 2 pooled multicentric prospective registries of consecutive patients with anterior AIS-LVO treated with mechanical thrombectomy (MT) between January 2016 and 2019. Patients with pretreatment and 24-hour posttreatment diffusion-weighted imaging (DWI) achieving successful recanalization, defined as expanded Thrombolysis in Cerebral Infarction Scale score of 2B, 2C, or 3, were included. ENT were assessed and IG was measured by voxel-based segmentation after DWI coregistration. Associations between number of CRA, ENT, IG, and 3-month outcome were analyzed. Results: Four hundred nineteen patients achieving successful recanalization were included. ENT occurrence was strongly correlated with increasing CRA (ρ = 0.73, p = 10 −4 ). In multivariable linear analysis, IG was independently associated with CRA (β = 1.6 per retrieval attempt, 95% confidence interval [CI] 0.97–9.74, p = 0.03) and ENT (β = 2.7 [95% CI 1.21–4.1], p = 0.03). Unfavorable functional outcome (3-month modified Rankin Scale score >2) increased with each additional CRA. IG was an independent predictor of unfavorable outcome (odds ratio 1.05 [95% CI 1.02–1.07] per 1-mL IG increase, p = 10 −4 ) in binary logistic regression analysis. Conclusions: Increasing number of CRA in acute stroke is correlated with an increased ENT rate and increased IG volume, affecting functional outcome even when successful recanalization is achieved. Classification of Evidence: This study provides Class II evidence that, for patients with acute stroke undergoing successful recanalization, an increasing number of CRA is associated with poorer functional outcome.